Jarilla–Coffea extract: a natural cosmetic product that improves eyelash and eyebrow growth in women - Alonso MR; Pérez Damonte S; Anesini C (Dove Medical Press, 2019)
María Rosario Alonso,1 Silvia Pérez Damonte,2 Claudia Anesini1 1Universidad de Buenos Aires, Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET), Instituto de Química y Metabolismo del Fármaco (IQUIMEFA), Department of Pharmacology, Facultad de Farmacia y Bioquímica, Buenos Aires, Argentina; 2CLAIM, José Bonifacio 717 (C1424 CHO) Ciudad Autónoma de Buenos Aires, Buenos Aires, Argentina Purpose: A combination of extracts, from two plant species, ie, Coffea arabica and Larrea divaricata (Jarilla) (ECOHAIR®), is being successfully used in Argentina as a cosmetic for hair recovery in androgenic and areata alopecia, and for eyelash and eyebrow growth. The objectives of this prospective study were to evaluate the capacity of Jarilla–Coffea extract gel of improving hair growth in relation to thickness, appearance of new hair, and hair length in comparison with a placebo in premenopausal and postmenopausal volunteers and to identify possible signs of ocular adverse local reactions related to the application of the gel.Volunteers and methods: An open-label, placebo-controlled, prospective study was performed in healthy premenopausal and postmenopausal women during a daily administration period of 2 months (eyebrow growth) and 3 months (eyelash growth). The thickness of hair was determined using a video microscope MedicalScope®. The appearance of new hairs and total area with hair in eyebrow and eyelash length were quantified using a photographic record with Fotofinder® (Germany). The number of volunteers presenting variation in growth of new hair and length were also recorded.Results: The product significantly increased the thickness of eyebrows (20% in 80% women) and eyelashes (19.44% in 100% of women). The gel also increased the appearance of new hairs, total area with hair, and length but there was no statistical difference between treatment and placebo.Conclusion: The gel was capable of improving growth of eyelashes and eyebrows by inducing principally hair thickening without causing local adverse effects in a high percentage of volunteers. Keywords: eyelash thickness, eyebrow thickness, plant extracts, menopause, adverse effects, cosmetic